(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: The objective of my study is to develop Relationship of Preoperative Surgical Delay to Mortality in Patients with Hip Fractures at 1year. Study design: Retrospective observational study Place and Duration of Study: We conduct this retrospective study in the department of Orthopedic and Spine Surgery, from January 2020 to December 2021. Methods: Patients divided into 3 groups according to the surgical timings from the time of injury. Group A surgery performed within 24 hours, Group B surgery performed between 24-48 hours and group C surgery performed after 48 hours and mortality is being checked in each group till 1-year post-operative time period by contacting each patient. Age, Gender, co morbidities, surgical procedure performed, fracture pattern (extracapsular, intracapsular) time of injury data was collected from registry of the hospital after taking permission from the authorities involved. Results: One hundred and fifty patients presenting with hip fractures were studied. Majority of our patients were females (n=85, 56.66%) and males (n=65,43%). Out of which 94 (62.6%) patients are included in group A, 34(22.6%) patients in group B, and 22 (14.66%) patients in group C. In group A 6 patients (6.3%) has mortality within 1 year. In group B 17 patients (50%) has mortality within 1 year. In group C 16 patients (72%) has mortality within 1 year. Conclusion: Mortality increases with surgical delay in hip fracture patients. Survival was higher for patients operated within 24h of admission.